The Effect of Problem-Solving Skills Training on the Anxiety of Female Candidates for Intrauterine Insemination Treatment - Elham Khoori; Fatemeh Zarekia; Shahram Mohammadkhani; Azizeh Ghaseminejad; Navisa Sadat Seyedghasemi (Golestan University of Medical Sciences, 2018)
Background: The success of therapeutic results of assisted reproductive techniques is related to several factors, including the extent of female anxiety. The aim of this study was to determine the effect of training problem solving skills on the anxiety of female candidates for intrauterine insemination in Moheb Yas Hospital in Tehran (2015). Methods: This experimental study was a two-group design (intervention and control) of pre-test and post-test type. The data collection tool was a sociodemographic form and Beck Anxiety Inventory. The samples comprised of 49 female candidates for assisted reproductive technique of intrauterine insemination, with the least Anxiety Score of eight from Beck Anxiety Inventory.  Based on this inventory, participants were homogenized in terms of different levels of anxiety and were randomly assigned into intervention and control groups. For intervention group, the problem-solving skills were trained for three sessions of 2-2.5 hours. Then, Beck's Anxiety Inventory was filled in both intervention and control groups, one day and 9 weeks after the end of the intervention. The data was analyzed in SPSS version 16, using the descriptive and analytical statistics (Mann-Whitney, Wilcoxon, and Paired t-test). Results: There was no significant difference in the anxiety score among the two intervention and control groups before intervention, whereas the anxiety score indicated a significant difference between the two groups (P=0.001) one day and 9 weeks after the end of the intervention. Training problem-solving skills significantly reduced the anxiety of the intervention group one day after the intervention, and the decrease also remained stable at 9 weeks after the end of the intervention (p = 0.001). Conclusion: By training problem-solving skills, we can reduce the anxiety among female candidates for intrauterine insemination.